Performance of bamboo sticks as steel reinforcement in reinforced concrete beam - Tan, Khye Fang (2016)
This research deals with the experimental study on the behaviour of bamboo sticks as steel reinforcement in reinforced concrete beams. A small section of treated and untreated bamboo samples were prepared to study the microstructure of each samples using scanning electron microscope (SEM). There are two types of chemical used which include black oxide primer and sodium hydroxide solutions with concentration of 5%, 10% and 15%. The physical properties which include density, initial moisture content, water absorption, compression and tension of bamboo were also investigated. Based on the results obtained, the structural testing on concrete RC beams, including the load deflection, cracking patterns and mode of failure were performed. A total of three (3) samples of concrete beams with compressive strength of 30 MPa were tested under four-point bending test, which included one steel RC beam acted as a control beam (CB), one bamboo RC beam (BR) and one bamboo steel RC beam (BSR). The beam had a cross section of 120 mm in width and 300 mm in depth as well as a total length of 1600 mm. By comparing with untreated bamboo, treated samples with sodium hydroxide solution shows the elongation of pore structures with 10% concentration of sodium hydroxide. However, the concentration which is greater than 10% has caused the pore structure to be damaged. The pore structures of treated bamboo samples with oxide primer are fully protected by the coating of oxide primer. The resulting SEM images show that there are no visible pore structures after treatment. Coating of oxide primer also ensures bamboo is water resistant. In terms of physical properties, bamboo has remarkable results for tensile in which it was recorded to be 10% of steel tensile stress. The compressive strength of one node bamboo was recorded to be significant in which it is 59% higher than zero node bamboo. In structural aspect, experimental studies show that bamboo reinforcement with proper adaptations in beam BSR has managed to achieve 46% of the capacity in steel reinforcement in control beam (CB). However, beam BSR which is partially reinforced with bamboo did not show any significant effect in terms of beam strength.